K Kearifan Lokal Dalam Tradisi Nganggung di Desa Sekar Biru: Kearifan Lokal Dalam Tradisi Nganggung di Desa Sekar Biru - Sela Puspita; Dessy Wardiah; Achmad Wahidy (LP2M UIN Abdul Muthalib Sangadji Ambon, 2024)
Local Wisdom is a noble value contained in the cultural wealth of traditions in community groups from generation to generation that are passed down from generation to generation. Therefore, people must understand the value contained in the traditions they carry out. Based on this, the problem in this study is how local wisdom in the nganggung tradition in the study of religious values and traditional values in the nganggung tradition. The purpose of this research is to know how to describe the local wisdom in the Nganggung tradition in the study of religious values and traditional custom values. The method used in this research is descriptive qualitative. The results showed that the Nganggung tradition has religious values, namely reciting prayers, listening to lectures, helping, and strengthening friendship. As for the value of traditional customs, namely that the nganggung tradition is a hereditary tradition that has been carried out by the Sekar Biru Village Community. The nganggung tradition has provisions for the day of implementation, food to be brought, as well as reading prayers and lectures that are tailored to the day of the nganggung implementation. Keywords: Local Wisdom, Nganggung Tradition, Religious Value, Customary Tradition Value.